Tanzania: stop that chain saw! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Uncontrolled and illegal felling of Tanzania s forests is costing the government USD 20 million in lost revenue, equivalent to half the sector s potential profits. Of the country s 33 million hectares of forest, two-thirds belong to the public...